Universal Current-Conveyor-Based Current-Mode Filters with Single Input and Three Outputs - Muhammad Taher Abuelma'atti; Amir Alam Farooqui (Active and Passive Electronic Components)
Universal active current-mode filters with single input and three outputs are presented. The proposed filters avoid the use of external feedback in any part of the circuit and use grounded resistors and grounded capacitors. The proposed circuits can simultaneously realize lowpass, highpass, and bandpass filter functions.